Production of Yarrowia lipolytica Nha2 Na+/H+ antiporter improves the salt tolerance of Saccharomyces cerevisiae - Papousková, K; Sychrová, H (Folia microbiologica, 2007)
Yarrowia lipolytica plasma-membrane Na+/H+ antiporter, encoded by the YlNHA2 gene, is a very efficient exporter of surplus sodium from the cytosol. Its heterologous expression in Saccharomyces cerevisiae wild-type laboratory strains increased their sodium tolerance more efficiently than the expression of ZrSod2-22 antiporter from the osmotolerant yeast Zygosaccharomvces rouxii.
Keywords: klonování DNA; rekombinantní proteiny; Recombinant Proteins; Saccharomyces cerevisiae; exprese genu; Cloning, Molecular; antifungální látky; Antifungal Agents; fungální proteiny; Salts; soli; Yarrowia; Na(+)-H(+) antiport; Fungal Proteins; Sodium-Hydrogen Exchangers; Gene Expression; Zygosaccharomyces